Analytical analysis and effect of scrambling on inter-relay interference in a tri-sectored LTE-A network. (2018) - Amin, Mehboob Ul; Sheikh, Javaid A.; Parah, Shabir A.; Bhat, Ghulam M.
The incorporation of relay nodes (RNs) in LTE networks for coverage and capacity enhancement generates some inter-relay interference. To mitigate this inter-relay interference in 4G-LTE-A standard, the effect of scrambling technique is discussed in this paper. This makes the proposed technique unique, in the sense that intra-relay distance becomes immaterial, unlike the existing techniques where it is mandatory to maintain a specific distance between the relay nodes of the same sector. A new analytical model for tri-sectorised hexagonal cellular networks is presented in this paper. The expectation values for signal-to-interference noise ratio (SINR) and through-put capacity for all the positions of access link are derived. Simulations are carried out on Matlab software to validate the theoretical analysis. The cumulative distribution function (CDF) curves for both SINR and through-put capacity of each link depict the performance of the proposed model.